Laparoscopy decreases the disparity in postoperative complications between black and white women after hysterectomy for endometrial cancer - Lee, Jessica; Gerber, Deanna; Aphinyanaphongs, Yindalon; Curtin, John P.; Boyd, Leslie R. (Gynecologic oncology, 2018)
Black race has been associated with increased 30-day morbidity and mortality following surgery for endometrial cancer. Black women are also less likely to undergo laparoscopy when compared to white women. With the development of improved laparoscopic techniques and equipment, including the robotic platform, we sought to evaluate whether there has been a change in surgical approach for black women, and in turn, improvement in perioperative outcomes. Using the American College of Surgeons' National Surgical Quality Improvement Project's database, patients who underwent hysterectomy for endometrial cancer from 2010 to 2015 were identified. Comparative analyses stratified by race and hysterectomy approach were performed to assess the relationship between race and perioperative outcomes. A total of 17,692 patients were identified: of these, 13,720 (77.5%) were white and 1553 (8.8%) were black. Black women were less likely to undergo laparoscopic hysterectomy compared to white women (49.3% vs 71.3%, p<0.0001). Rates of laparoscopy in both races increased over the 6-year period; however these consistently remained lower in black women each year. Black women had higher 30-day postoperative complication rates compared to white women (22.5% vs 13.6%, p<0.0001). When laparoscopic hysterectomies were isolated, there was no difference in postoperative complication rates between black and white women (9.2% vs 7.5%, p=0.1). Overall black women incur more postoperative complications compared to white women undergoing hysterectomy for endometrial cancer. However, laparoscopy may mitigate this disparity. Efforts should be made to maximize the utilization of minimally invasive surgery for the surgical management of endometrial cancer. •Rates of laparoscopy for the treatment of endometrial cancer are lower in blacks.•Blacks have higher BMIs and have more preoperative comorbidities than whites.•The rates of postoperative complications after any hysterectomy are higher in blacks.•The rates of postoperative complications after laparoscopic hysterectomy are similar.